AB1302C SERUM IMMUNOGLOBIN G4 LEVEL IN DIFFERENT TYPES OF MALIGNANCY WITHOUT IMMUNOGLOBIN G4 RELATED DISEASE. (June 2019) - Zhang, Yanli; Liao, Zetao; Jiang, Yutong; Qing, LV; Tu, Liudan; Guo, Xinghua; Lin, Zhiming; Gu, Jieruo
Abstract : Background: High levels of serum immunoglobulin G4 (IgG4) would comprise a useful diagnostic tool in IgG4-related disease (IgG4-RD), but little information is available about IgG4 in conditions other than IgG4-RD such as malignancies. Previous studies indicate that IgG4-RD is a strong risk factor for malignancy development. Objectives: The aim of this study is to evaluate the level of serum IgG4 in different malignancy without IgG4-RD. Methods: 90 patients with malignancy were enrolled between March 1 st and August 30 th, which have been excluded with IgG4-RD. All samples were collected before treatment. Diagnosis of malignancy was determined by histological result. The levels of serum IgG4 were determined by nephelometric assay. The cut-off value of serum IgG4 was 201 mg/dl. We compared the levels of serum IgG4 among patients with different types of malignancy. Results: (1) Among the 90 patients, 18 patients were gallbladder carcinoma, 6 patients were lung carcinoma, 34 patients were liver carcinoma, 6 patients were gastrointestinal carcinoma, and 19 patients were pancreatic carcinoma. 68 (75.56%) patients were male and mean age was 52.8± 15.5 yrs. The mean value of serum IgG4 was 146.7±147.6 mg/dl, and 21 (23.3%) of patients have elevated serum IgG4. (2) Serum IgG4 level in gastrointestinal carcinoma is the highest (237.8±50.92 mg/dl), but the sample is too small. Serum IgG4 level in liver carcinoma was higher than other types of malignancy (180.5 ± 32.04 mg/dl. vs gallbladder carcinoma 114.4 ± 15.01 mg/dl, p<0.01. vs pancreatic carcinoma 91.63 ± 19.89 mg/dl, p<0.01. vs lung carcinoma 67.47 ± 11.75 mg/dl, P<0.01). Conclusion: Elevated serum IgG4 level is common in patients with malignancies, while patients with liver carcinoma have significant higher serum IgG4 level than those with gallbladder carcinoma, pancreatic carcinoma and lung carcinoma. This suggests that IgG4 may have different role in different types of tumor. Disclosure of Interests: None declared